Relationship between variables and attributes for organizational goals model - Tengku Adil Tengku Izhar; Torab Torabi; M. Ishaq Bhatti (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
The purpose of this paper is to develop and validate the data- to- organization goal approach relationship. This is because data is very important for organization toward future performance. It is important to identify the type of data within organization in order to support the main organization goal. This paper concern the relationship involve between data and organization goal. In order to achieve this purpose, five main variables are identified: organization goal, sub-goals, actions, data input and data output. In additional, the paper focused on the possible relationship between variables and attributes within organization goal. The analytical concept of the relationship is developed and a simple case study is implemented to support the discussion.
Keywords: 650; actions; attributes; organizational goals; sub-goals; variables